Uji Kompetensi Berbahasa Jawa Berbasis Virtual Assessment untuk Mahasiswa Pendidikan Bahasa dan Sastra Jawa - Supriadi, Didik (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Testing a competency requires thoroughness on the character of scientific studies. These criteria are used as a benchmark for assessment which is realized in the form of a variety of measuring instruments. The challenge is that the measuring instruments that are made still contain learning elements, not just looking for the weaknesses and strengths of the test takers. The design also needs an agreement between the organizer and the test takers, so that the activities run comfortably. This makes the exam more functional, useful, and doesn't waste anyone's time. This is the essence of learning. Developing a Javanese language competency test tool like this needs to be realized. The method used is structured through a virtual assessment approach. This approach contains (a) the concept of assessement, (b) orientation of the assessement, (c) management assesement, (d) assessment of the assessment, (e) analysis of the assessment, and (f) conclusion of the assessment. These six things produce data about the quality of student competencies. A total of 100 multiple choice questions are composed of 5 competency elements, namely (a) cultural science, (b) linguistics, (c) literature, (d) education, and (e) writing scientific papers. Meanwhile, 4 essay questions contain their scientific work ideas. Questions are packaged with online media. Conceptually, students' abilities have been identified. So in conclusion, a realistic approach is still needed so that it is able to generate or even strengthen potentials that are not recorded by written measuring instruments. This is a conclusion that contains suggestions for clinical supervision for maximum results.